Membangun Rasa Semangat kepada Anak Panti agar Lebih Meningkatkan Minat Membaca - Triana, Angelique; Fajar Utama; Asbi, Erni Asneli (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2024)
This article aims to examine the importance of a special approach in increasing orphanage children's interest in reading. The methods used were literature review and field study on orphanage children. The results showed that the right approach, such as the use of storybooks and fun learning methods, succeeded in building enthusiasm and increasing the reading interest of the orphanage children. The study emphasizes the importance of support in providing orphanage children with access to literacy and good education to prepare them for active participation in society. The research provides insights into effective strategies to improve the literacy and education of orphanage children, which can be useful for educators, caregivers and policy makers in developing better literacy programs.